The consequence of neuromuscular training on electromyography activity of lateral compartment muscles after ankle lateral ligament injury in athletes - Deivendran, Kalirathinam; Hairul Anuar, Hashim; Taran, Singh; Mohamed Saat, Isma (2017)
The ankle is one of the most common sports injuries and is also the most frequently re-injured. In the majority of cases, the ankle rolls inwards (inversion) under the weight of the rest of the body, resulting in damage to the ligaments on the outside of the ankle. The purpose of this study was to evaluate the role of peripheral afferent information from the lateral ankle ligaments in spatial and temporal muscle activation characteristics during an inversion perturbation dynamic stability. Twenty athletes volunteered to participate in this study, who sustained a lateral ankle sprain who were recruited for participation in this study. The subjects participated in a variety of collegiate sports were included in the study. The results indicated no statistically significant differences in the mean firing time between the control and experimental group for both the peroneus longus (t12 = 1.24, p = 0.238) or the tibialis anterior (t12= 0.75, p = 0.467) muscles. The results also showed no significant differences to exist between the tibialis anterior and peroneal muscles in both the control group (t= 2.31, p = 0.039) and experimental group (t12 = 2.13, p = 0.054) ankles. The results of the present investigation demonstrate that spontaneous reflex response time of the anterior tibialis and peroneal muscles do not differ between the control group ankle vs. the experimental group ankle. The inclusion of a comprehensive rehabilitation program following injury may have played a critical role in the results of this study.